An Open Trial of Morning Bright Light Treatment Among US Military Veterans with Chronic Low Back Pain: A Pilot Study. Issue 4 (10th September 2018) - Burgess, Helen J; Rizvydeen, Muneer; Kimura, Momoko; Pollack, Mark H; Hobfoll, Stevan E; Rajan, Kumar B; Burns, John W
Abstract: Objective: To examine the feasibility, acceptability, and effects of a home-based morning bright light treatment on pain, mood, sleep, and circadian timing in US veterans with chronic low back pain. Design: An open treatment trial with a seven-day baseline, followed by 13 days of a one-hour morning bright light treatment self-administered at home. Pain, pain sensitivity, mood, sleep, and circadian timing were assessed before, during, and after treatment. Setting: Participants slept at home, with weekly study visits and home saliva collections. Participants: Thirty-seven US veterans with medically verified chronic low back pain. Methods: Pain, mood, and sleep quality were assessed with questionnaires. Pain sensitivity was assessed using two laboratory tasks: a heat stimulus and an ischemia stimulus that gave measures of threshold and tolerance. Sleep was objectively assessed with wrist actigraphy. Circadian timing was assessed with the dim light melatonin onset. Results: Morning bright light treatment led to reduced pain intensity, pain behavior, thermal pain threshold sensitivity, post-traumatic stress disorder symptoms, and improved sleep quality ( P < 0.05). Phase advances in circadian timing were associated with reductions in pain interference ( r = 0.55, P < 0.05). Conclusions: Morning bright light treatment is a feasible and acceptable treatment for US veterans with chronic low back pain. Those who undergo morning bright light treatment may show improvements in pain, pain sensitivity, and sleep. Advances in circadian timing may be one mechanism by which morning bright light reduces pain. Morning bright light treatment should be further explored as an innovative treatment for chronic pain conditions.